Clinical utility of targeted treatments in the management of epithelial ovarian cancer - Twu C (Dove Medical Press, 2012)
Cheryl Twu,1 Ernest S Han21Department of Women’s Health, Arrowhead Regional Medical Center, Colton, CA, USA; 2Division of Gynecologic Oncology, City of Hope, Duarte, CA, USAAbstract: Epithelial ovarian cancer is typically found in its advanced stages, where a combination of surgical debulking and platinum/taxane-based chemotherapy is recommended. Although over 70%–80% of patients achieve remission, a significant proportion develop recurrence of their disease. Additional cytotoxic chemotherapy, as well as surgery, is typically used to manage disease recurrence. Therapies that target specific pathways in cancer cells are rapidly developing in the laboratory and are increasingly being studied in patients with ovarian cancer. We review the current status of novel therapies in the management of epithelial ovarian cancer.Keywords: angiogenesis, polyadenosine ribose pathway inhibitors, epidermal growth factor receptor, folate inhibitors